2013
DOI: 10.2474/trol.8.22
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Trace Water in a Hydrogen Environment on the Tribological Properties of Pure Iron

Abstract: The authors have clarified that trace impurities such as water and oxygen inevitably contained in a hydrogen environment influence friction and wear of metallic materials substantially and even often govern them. In this study, an experimental technique was devised to enable sliding tests in a hydrogen environment which contains controlled concentration of water and virtually no oxygen as impurities. By comparing data of Fe sliding tests between this study and our previous studies, the influences of water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
6
20
0
Order By: Relevance
“…However, in many articles about friction and wear experiments, the relative humidity of the environment is seldom controlled [1]. Previous researchers found that friction force and wear in sliding can be influenced even by extremely low level as several ppm concentrations of water [2][3][4][5]. The presence of adsorbed water due to the atmospheric humidity on the surface of a material can improve or deteriorate the tribological performances [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, in many articles about friction and wear experiments, the relative humidity of the environment is seldom controlled [1]. Previous researchers found that friction force and wear in sliding can be influenced even by extremely low level as several ppm concentrations of water [2][3][4][5]. The presence of adsorbed water due to the atmospheric humidity on the surface of a material can improve or deteriorate the tribological performances [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Trace water in purified gases can generate problems at use point such as ghost peaks in gas chromatography, and defect in semiconductor products like loss of light emitting efficiency in LEDs [15]. The effect of few ppmv of trace water in hydrogen environment on the tribological effects has also been detailed [16]. Quality control analysis of gases used in an industry is important at each stage, including production, transfer, and use of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Usually, Karl Fischer titration and gas chromatography are used for the determination of water contents. [1][2][3][4][5][6][7][8][9][10][11][12] Usually, Karl Fischer titration and gas chromatography are used for the determination of water contents.…”
Section: Introductionmentioning
confidence: 99%